2004
DOI: 10.1093/glycob/cwi026
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-3 and soluble fibrinogen act in concert to modulate neutrophil activation and survival: involvement of alternative MAPK pathways

Abstract: Galectin-3 (Gal-3), a member of a family of highly conserved carbohydrate-binding proteins, has recently emerged as a novel cellular modulator at inflammatory foci. Here we investigated the effects of Gal-3 on central effector functions of human neutrophils, including phagocytosis, exocytosis of secretory granules, and survival. We examined the effects of Gal-3 alone or in combination with soluble fibrinogen (sFbg), an extracellular mediator that plays a key role during the early phase of the inflammatory resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
3
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 98 publications
(79 citation statements)
references
References 55 publications
(61 reference statements)
4
70
3
2
Order By: Relevance
“…Furthermore, only Gal-4 induces nonapoptotic PS exposure independent of intracellular Ca 2ϩ mobilization in neutrophils (26), suggesting the existence of at least two separate pathways regulating nonapoptotic PS exposure. In contrast to the present study, previous results demonstrated that transient treatment of resting neutrophils with Gal-3 enhanced spontaneous apoptosis when analyzed following prolonged incubation (65). However, because high levels of free glycan are unlikely to efficiently disengage Gal-3 once bound to neutrophils, we felt that evaluating the effect of Gal-3 on neutrophil viability and PS exposure following continual treatment with Gal-3 would more appropriately reflect Gal-3 interactions with neutrophils in vivo.…”
Section: Discussioncontrasting
confidence: 91%
“…Furthermore, only Gal-4 induces nonapoptotic PS exposure independent of intracellular Ca 2ϩ mobilization in neutrophils (26), suggesting the existence of at least two separate pathways regulating nonapoptotic PS exposure. In contrast to the present study, previous results demonstrated that transient treatment of resting neutrophils with Gal-3 enhanced spontaneous apoptosis when analyzed following prolonged incubation (65). However, because high levels of free glycan are unlikely to efficiently disengage Gal-3 once bound to neutrophils, we felt that evaluating the effect of Gal-3 on neutrophil viability and PS exposure following continual treatment with Gal-3 would more appropriately reflect Gal-3 interactions with neutrophils in vivo.…”
Section: Discussioncontrasting
confidence: 91%
“…It is intriguing that, despite similar carbohydrate specificities, galectins 1 and 3 can trigger different signal transduction pathways on different cell types. In this sense, we have recently demonstrated that galectin-3 induces p38 but not ERK1/2 phosphorylation in human primed neutrophils (48). However, in the present study, we demonstrate that galectin-1 may trigger an ERK1/2-but not p38-dependent signal transduction pathway in human monocytes.…”
Section: Discussioncontrasting
confidence: 70%
“…Galectin-3-mediated ligand clustering triggers neutrophils to phagocytose, produce reactive oxygen species, release proteases, and secrete interleukin (IL)-8 [15,16,30]. In addition, galectin-3 induces mast cell degranulation: recent studies have revealed a critical role for this protein in mast cell function since galectin-3-deficient mast cells show reduced histamine release and IL-4 secretion [14].…”
Section: Galectin-glycoprotein Lattices In Innate Immunitymentioning
confidence: 99%